THE IMPORTANCE OF NURSES’ KNOWLEDGE OF BRAZILIAN SIGN LANGUAGE (LIBRAS) FOR UNIVERSAL CARE IN PRIMARY HEALTH (REMUNOM, 2026)
Introduction: Effective communication is essential to ensure that the deaf population receives quality health care, whose main form of communication is the Brazilian Sign Language (LIBRAS). Objective: To present the importance of nurses’ knowledge of LIBRAS for universal care in primary health care. Materials and method: This is a bibliographic, descriptive, and qualitative study, based on scientific publications indexed in the SciELO, PubMed, LILACS, Google Scholar, and Virtual Health Library databases, considering studies published in the last ten years. Results: The results show that, without proficiency in LIBRAS, nursing professionals constitute a communication barrier, impairing anamnesis, patient safety, treatment adherence, and humanized care. Scientific contribution: It was identified that the main obstacles faced include shortcomings in academic training, lack of continuing education, and scarcity of LIBRAS interpreters. On the other hand, strategies such as the use of technological resources, the effective integration of LIBRAS into the academic nursing curriculum, and the presence of interpreters within health teams may reduce communication barriers in care delivery. Final considerations: It is considered that training in LIBRAS should not be seen only as a professional differential, but as an ethical and legal requirement for the fulfillment of the principles of the Unified Health System (SUS), especially equity and comprehensiveness of care.